Teori Konstruktivisme Dalam Dunia Pembelajaran - Nabiila Tsuroyya Azzahra; Septa Nur Laila Ali; M Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article discusses the implementation of constructivism theory in the world of learning, especially at the elementary school level. The study uses a literature review method by examining various literatures related to generative constructivism. The results of the study show that constructivism emphasizes the active role of students in building knowledge through direct experience and social interaction. Teachers act as facilitators who help students construct understanding, not just transfer knowledge. Constructivism-based learning requires students to think actively, compose concepts, and take responsibility for their learning outcomes. The characteristics of constructivism learning include learning that is relevant to real life, collaborative, and student-centered. In conclusion, the application of constructivism theory can increase students' activity, creativity, and independence in the learning process.